Design and Manufacturing of 3d Printed Models as a Complement for Medical Histology Practical Classes - Osses-Mc Intyre, M; Godoy-Guzman, C; Padilla-Meza, J (SOC CHILENA ANATOMIA, 2022)
Traditionally, Histology has relied on the analysis of histological slides through the microscope for its teaching. In this sense, one of the main obstacles faced by students when analyzing tissues is to extrapolate a two-dimensional image to a three-dimensional (3D) structure. 3D printing makes it possible to overcome this limitation, making it possible to manufacture teaching material with the required characteristics with a high degree of detail and low cost. The objective of this work was to design and manufacture 3D printed models as a complement for the practical classes of Medical Histology. 3D printed models of the ultrastructure of the glomerular filtration barrier (GFB) in its normal state and nephrotic syndrome were fabricated. In addition, a model of the muscular layer of the human esophagus was fabricated emphasizing the helical arrangement of its muscle fibers. The epidermis models allowed the identification of its different layers: stratum corneum, stratum granulosum, stratum spinosum, and stratum basale. Among the benefits derived from 3D printing of models, we can highlight the low economic cost of manufacturing, biosafety and potential to favor the learning and teaching of Histology. However, it is necessary to analyze the perception and benefit on student learning derived from the application of the models by means of quantitative and qualitative evaluation techniques.